Degree of fear of needles and preferred allergy immunotherapy treatment among children with allergic rhinitis: caregiver survey results - Rance, Karen; Blaiss, Michael; Gupta, Payel; Nolte, Hendrik; Scott, Erin P.; Gardner, Donna D. (Frontiers in Pediatrics, 2024)
Introduction: A child's fear of needles may impact the preferred route of allergy immunotherapy (AIT) when choosing between subcutaneous immunotherapy (allergy shots) or sublingual immunotherapy (SLIT). A survey was conducted to understand caregiver health-seeking behavior for children with allergic rhinitis with or without conjunctivitis (AR/C) and explore if fear of needles impacted AIT decisions. Methods: Caregivers of children ages 5-17 years with AR/C were recruited from the Dynata US research panel to participate in an online survey from May-June 2023. The survey received institutional review board exemption status. SLIT-tablets were described as "under-the-tongue tablets". Results: About a third (34%) of surveyed caregivers (n=437) reported their child had a severe fear of needles and 47% reported moderate fear. Of surveyed caregivers, 53% and 43% reported they had discussed allergy shots and SLIT-tablets, respectively, with their child's physician. SLIT-tablets were preferred by 84% of caregivers; 6% preferred injections and 10% had no preference. Caregivers of children with a severe fear of needles had the highest preference for SLIT-tablets (95%) vs injections (2%); 85% and 60% of caregivers of children with moderate and low fear, respectively, preferred SLIT-tablets. Among caregivers of children with a severe fear of needles, a higher percentage agreed that their child would welcome taking SLIT-tablets than that their child would accept taking an ongoing series of allergy shots (93% vs 43%, respectively). Conclusions: Most caregivers preferred SLIT-tablets over allergy shots for their child with AR/C. Preference for SLIT-tablets corresponded with the child's degree of fear of needles. Fear of needles should be included in AIT shared decision-making conversations.